Análisis del comportamiento agronómico del cultivo de maíz, considerando fenología y densidad de siembra, con el uso de tecnología aeroespacial y espectral - Angulo Cedeño, Carlos Javier (2022)
The use of technology in agriculture helps farmers increase productivity in their crops, obtaining multispectral images allows estimating the health status of the crop, evaluating the nutritional status, water stress, chlorophyll content. The main objective of this research is to analyze the agronomic behavior of corn cultivation, considering the phenology and planting density, using spectral and aerospace technology.